Effects of P₂O₅ and sintering temperature on morphological, physical, and mechanical properties of SiO₂-Na₂O-CaO-P₂O₅ glass-ceramic - Baharuddin Pallan, Nur Fadilah (2018)
The great varieties of compositions and microstructures with specific technological properties have allowed glass-ceramics to be used in a wide range of applications. Materials fabricate from vitreous and ceramic wastes nowadays have been widely used in order to minimize the cost of production, eco-friendly materials, and reduce the landfill disposal matters. SiO₂-Na₂O-CaO-P₂O₅ (SNCP) composition was selected since lack of study has been discussed on SNCP glass-ceramic from waste material. This approach and opportunity have been taken to investigate further about the materials properties and compare with previous study. The main waste raw materials used are clam shells (CS) and soda-lime-silica (SLS) glass bottle. There are four types batch formulation of SNCP glass-ceramic that have been fabricated via conventional melt-quenching technique and solid state sintering. Each type of SNCP series were varied with different NaCO₃ to P₂O₅ weight percentage and samples were sintered at temperature 550−950 °C. Samples were sintered to discover effect sintering temperature evolving on morphological, physical, and mechanical properties of SNCP are highlighted in this study. The XRD results before sintering have been confirmed the existence of amorphous-crystalline phases on SNCP 1 and SNCP 4 samples while amorphous phase formation corresponding to SNCP 2 and SNCP 3 samples. The full crystallization for SNCP 1 and SNCP 4 started to occur at 650 °C while for SNCP 2 and SNCP 3 at sintering temperature 750 °C. Overall, the glass transition temperature (Tg) started at the range of 550−580 °C and the glass crystallization temperature (Tc) started from 600 °C to 743 °C. The existence of P2O5 in SNCP glass-ceramic is attributed to glass crystallization correlated with high intensity of crystallization peak and enhanced volume nucleation. The microstructural study observation showed SNCP 1 sample at 550−950 °C have agglomerated grain and porosity decreased which produce fine and uniform grain as the sintering temperature increases while the SNCP 2 until SNCP 4 showed less porosity, fine and uniform grain at 550−750 °C produced high densification microstructural. The density values (2.097−2.726 g/cm3) for SNCP 1−SNCP 4 obtained below the glass crystallization temperature at 550−750 °C contribute to excellent mechanical properties. SNCP 3 obtained the highest hardness (631 HV) at 650 °C than SNCP 1 (332 HV). The highest compressive strength in SNCP 1 (free- P2O5) is 49.66 MPa with Young’s modulus value 0.678 GPa at sintering temperature 650 °C while SNCP 3 obtained the highest compressive strength (33.44 MPa) with Young’s modulus value 0.882 GPa. Both samples have higher Young’s modulus values when comparing from previous study (0.05−0.5 GPa) for the cancellous bone implantation. The influence of morphological and physical properties on SNCP 3 sample at sintering temperature 650 °C contribute to excellent mechanical strength properties.